In-vitro starch and protein digestibility and proximate composition of soybean flour fermented with lactic acid bacteria (LAB) consortia - Ogodo, Alloysius Chibuike; Ugbogu, Ositadinma Chinyere; Onyeagba, Reginald Azu; Okereke, Hope Chukwuemeka (Agriculture and Natural Resources, 2018)
The changes in the proximate composition, in-vitro starch/protein digestibility and microbiological quality of lactic acid bacteria (LAB)-fermented soybean flour were evaluated at 12 h intervals for 48 h. Soybean was processed into flour and fermented with LAB-consortium previously isolated from maize (Lactobacillus plantarum WCFS1+Lactobacillus rhamnosus GG ATCC53/03 + Lactobacillus nantensis LP33 + Lactobacillus fermentum CIP102980 + Lactobacillus reuteri DSM 20016), and sorghum (Pediococcus acidilactici DSM 20284 + Lactobacillus fermentum CIP102980 + Lactobacillus brevis ATCC14869 + Lactobacillus nantensis LP33 + Lactobacillus plantarum WCFS1). The flour was also fermented naturally for comparison. There was significant (p < 0.05) increase in the moisture content as the fermentation time increased and ranged from 10.32 ± 0.05% to 10.98 ± 0.04%. The ash and protein contents also increased significantly (p < 0.05) with the highest increase occurring in the samples fermented with lactic acid bacteria consortia. The lipid, crude fibre and carbohydrate contents decreased with increasing fermentation time. In-vitro starch digestibility increased significantly (p < 0.05) with increasing fermentation time from 71.36 ± 0.20% to 80.11 ± 0.02%. In-vitro protein digestibility increased significantly (p < 0.05) from 85.40 ± 2.46% to 93.56 ± 2.50%. Bacteria load increased as fermentation time increased. Fungal growth was only observed in natural fermentation. The occurrence of isolates showed that only starter organisms were isolated from the consortia fermentation set-ups. This study has shown that combination of LAB in fermentation of soybean flour can improve their nutritional value and digestibility.